Repeated bouts of eccentrically biased endurance exercise stimulate salivary IgA secretion rate - McKune, Andrew J; Starzak, Dorota; Semple, Stuart J (Biology of Sport, 2015)
To determine the salivary secretory immunoglobulin A (sIgA) response to repeated bouts of unaccustomed, downhill running (eccentrically biased) and examine potential protective immunological adaption from a repeated bout effect. Eleven active but untrained males (age: 19.7±0.4 years; VO2peak: 47.8±3.6 ml · kg-1 · min -1) performed two 60 min bouts (Run 1 and Run 2) of downhill running (-13.5% gradient), separated by 14 days, at a speed eliciting 75% of their VO2peak on a level grade. Saliva samples were collected before (baseline), immediately post exercise (IPE), and every hour for 12 h and every 24 h for 6 days after each run. Salivary sIgA concentration was measured and sIgA secretion rate was calculated. Results were analysed using repeated measures ANOVA (12 h period: 2x14; 24 h intervals: 2x7; p ≤ 0.05) with Tukey post-hoc tests where appropriate. Results are reported as means ± SE. There was a significant (p < 0.0001) interaction effect for sIgA secretion rate, IPE, with higher values after Run 2, as well as a significant (p < 0.01) time effect with elevated levels IPE and between 24 h and 144 h. There was a run effect (p < 0.0001), with the sIgA secretion rate significantly higher after Run 2. Repeated bouts of unaccustomed, eccentrically biased exercise induced alterations in the salivary sIgA secretion rate. This may serve as a protective mucosal adaptation to exercise-induced tissue damage.